E-cath: um sistema para telemedicina em hemodinâmica utilizando redes de baixa velocidade - Bernardo Moreira de Faria (2003)
e-Cath addresses a low cost solution for telemedicine in Cath Labcenters based on standard low speed and low QoS Internetconnections. It aims to provide remote access to exam reports anddata, peer to peer remote case discussion second opinion anddiagnosis explanation and remote exam observation. Severalprocesses are proposed, including video and image transmission andmanipulation, synchronization and session control betweenparticipants. Other relevant aspect is data security and privacy. Thework include a requirement analysis of the whole system and aprototype of the peer to peer remote case discussion, initial focus of theimplementation.